PEMANTAUAN DAN EVALUASI GARAM BERYODIUM SEBAGAI SALAH SATU UPAYA UNTUK MENINGKATKAN CAKUPAN DAN KUALITAS PROGRAM PENANGGULANGAN GAKY DI KABUPATEN BANYUMAS - Endo Dardjito; Edwi Saraswati (Persagi, 2005)
ABSTRACT Background:Although the prevalence of iodine deficiency disorders in Banyumas as measured by total goitre rate, fro 27% (1980) to 3,5 % (1996) the prevalence at IDD sti high in some subdistrict. Therefore, there is a need to monitor iodine content in salt distributed in the area. Objectives: To determine iodine content in salt consumed by households of elementary school children. Methods: A total of samples 1260 pack of ionized salt were randomly selected from 60 elementary school in Banyumas Regency. The data collection was done in 2003th. The quality of iodized was done by titration test and iodine test. Results: In general, the contain of iodium in iodized salt is good enough that is 75,6%, most of the type of iodized salt (98,4%) have trade mark, most of the type of iodized salt (82,9%) is granulated salt and most of iodized salt (74,2%) in the market has number of the trade mark. Conclosions: The quality of iodized salt is good. [Penel Gizi Makan 2005,28(1): 16-22] Keywords: iodized salt, titration test, iodine test